(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Measles remains a major cause of morbidity and mortality among children under five years in low-income settings globally, despite the availability of effective vaccination. Slum areas face amplified risk due to overcrowding, poor sanitation, and limited healthcare access. Objectives: To assess the effectiveness of measles vaccination, identify associated risk factors, and determine complications in children under 5 years residing in slum areas of Karachi. Methods: A cross-sectional study was conducted with 500 children aged 9 to 59 months from Karachi slums selected via stratified random sampling. Data on vaccination status, socio-demographics, risk factors, and measles complications were collected through interviews and health records. Descriptive statistics and inferential analyses including chi-square tests and logistic regression were performed. Results: Measles vaccination coverage was 68%. Vaccinated children had significantly lower incidence of measles infection (OR=0.28; 95% CI: 0.18-0.44; p<0.001) and fewer complications like pneumonia and diarrhea. Risk factors significantly associated with measles incidence included under nutrition (p=0.002), lack of maternal education (p=0.015), and inadequate sanitation facilities (p=0.01). Logistic regression confirmed vaccination and sanitation as protective factors. Conclusions: Measles vaccination effectively reduces measles infections and complications among children in Karachi slums, though coverage gaps remain. Public health strategies should enhance vaccination outreach, nutrition, and sanitation to reduce disease burden.